2006
DOI: 10.1002/eji.200535270
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A is required for M‐CSF‐dependent macrophage proliferation

Abstract: The immunosuppressor sanglifehrin A (SfA) is a member of a family of immunophilin cyclophilin A-binding molecules and does not inhibit calcineurin activity. Sanglifehrin A inhibits M-CSF-dependent macrophage proliferation by arresting the G1 phase of the cell cycle but does not affect cell viability. This immunosuppressor exerts its action on proliferation by inactivating cyclin-dependent kinase 2 (Cdk2) activity. Moreover, c-myc expression is also repressed. In the early steps of M-CSF signaling, SfA inhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 56 publications
4
23
0
Order By: Relevance
“…2A). A previous report revealed that cyclophilin A (CypA), which shows functional similarity to TgCyp18, contributes to macrophage proliferation through activation of the Raf-1/MEK/extracellular signal-regulated kinase pathway and regulation of cyclin-dependent kinase activities, which are required for cell cycle progression (36). Cytokines and/or soluble factors might contribute to the cell proliferation via a CCR5-independent manner, but determination of the potential roles of the factors is needed.…”
Section: Discussionmentioning
confidence: 99%
“…2A). A previous report revealed that cyclophilin A (CypA), which shows functional similarity to TgCyp18, contributes to macrophage proliferation through activation of the Raf-1/MEK/extracellular signal-regulated kinase pathway and regulation of cyclin-dependent kinase activities, which are required for cell cycle progression (36). Cytokines and/or soluble factors might contribute to the cell proliferation via a CCR5-independent manner, but determination of the potential roles of the factors is needed.…”
Section: Discussionmentioning
confidence: 99%
“…One microgram was retrotranscribed using Moloney murine leukemia virus reverse transcriptase RNase H Minus (Promega) and real-time PCR was performed as described (24). Data were expressed as relative to the ␤-actin expression in each sample.…”
Section: Rna Extraction and Real-time Rt-pcrmentioning
confidence: 99%
“…Cyp-A was originally discovered as an intracellular ligand for cyclosporin A, an immunosuppressant (Handschumacher et al, 1984), but other functions have also been suggested. The secreted form of Cyp-A is a potent chemoattractant for macrophage colony-stimulating factor (MCSF)-dependant macrophages (Comalada et al, 2003;Sà nchez-Tilló et al, 2006), monocytes (Galat, 1993;Payeli et al, 2008), neutrophils (Sherry et al, 1992), eosinophils (Xu et al, 1992), and T cells (Kasinrerk, 1999). This molecule is involved in the adhesion of monocytes/macrophages to the extracellular matrix (Yang et al, 2008) and the migration of murine bone marrow cells (Khromykh et al, 2007).…”
Section: Discussionmentioning
confidence: 99%